Cibercultura e ensino de ciências: questões contextuais a partir da disciplina Tecnologia da Informação e Comunicação (tics) no curso de educação do campo ênfase, em ciências da natureza - CORDEIRO, Leonardo Zenha (Universidade Federal Rural do Rio de Janeiro, 2022)
The text approaches the teaching of science, taking as reference the social and technical changes from the reality of the students of the Course of Field Education (emphasis in Nature Sciences), understanding the cyberculture as one of the fundamental elements to think about teaching and its changes in the current period. The proposal is part of a reflection based on the subject of Information and Communication Technology (ICTS), having as background the implications of these in the teaching of science, one of the disciplines that graduates of this course can act. The text seeks to make explicit conceptual and contextual elements in this field of study, cyberculture and science teaching present in the field education, in face of daily living in and outside the classroom, especially in the undergraduate course in Field Education, which is underway in the region of the Transamazônica highway and Xingu River, west of the state of Pará.The reflections point to the non-separation of school time and community time in the learning processes as an innovative element that is enhanced through the use of ICTs.